Brown Slime, the Silver Tsunami, and Apocalyptic Demography: The Importance of Ageism and Age Relations. (June 2020) - Calasanti, Toni
Despite our awareness of ageism, sociologists rarely examine either old age as a disadvantaged status or age relations as an inequality that intersects with others. I show how this exclusion limits our theory and our work for social justice. I outline age relations and two kinds of ageism that maintain them, one of them obvious and one more insidious and often found in works of social science. Age relations matter not only to our theory and research, but also to debates over social safety nets and other public policy. I focus on the example of the threatening "silver tsunami" in apocalyptic demography and the construction of dependence through the use of age dependency ratios. Neglect of ageism and age relations keeps sociologists unable to contribute to critical policy debates that shape lives across age groups. Researching how age relations intersect with other inequalities yields findings that contradict what many take for granted about such issues as poverty or sexual harassment. Sociology must focus more than it has on an inequality that shames and excludes elders from full citizenship and robs them of control over their lives. We all face that situation if we live long enough.